Injection of hydrogen gas stimulates acid mine drainage treatment in laboratory‐scale hydroponic root mats. Issue 8 (25th July 2016) - Richter, Juliane; Wiessner, Arndt; Zehnsdorf, Andreas; Müller, Jochen A.; Kuschk, Peter
Abstract : The environmentally benign disposal of acid mine drainage (AMD) is still a technical challenge. In the present study, artificial AMD was treated in a laboratory‐scale floating hydroponic root mat of soft rush, Juncus effusus . This ecotechnological system was operated with hydrogen injection and water recirculation but without an external carbon supply. It achieved a mean increase of ΔpH = 3.3 up to pH ≈ 8.2, high sulfate removal of up to 87%, and efficient removal of iron (100%), aluminum (99.8%), manganese (97.4%), and zinc (99.6%). Sulfide was not detected in the outflow. Treatment performance correlated with the amount of hydrogen loading. Daily oscillations of the redox potential up to amplitudes of Δ E h ≈ 450 mV in a mean range of E h ≈ −150 to +300 mV indicated a correlation of plant physiology and removal processes. Apparently, sulfate and metal removal were the result of chemolithotrophic microbial sulfate reduction supported by the externally provided H2 and chemoorganotrophic sulfate reduction driven by rhizodeposits. Bicarbonate generated in the microbial transformation of such plant‐derived organic carbon contributed to pH neutralization. The effluent's pH increase was governed further by recirculation of the treated AMD. The flow regime and the injection of hydrogen at the ground of the root mat caused concentration gradients where the most efficient removal occurred in the deepest zone of the root mat. Further investigations should target long‐term stability, plant growth dynamics, load variations, balances of carbon and sulfur, the removal of H2 S and metal precipitates from the system as well as efficient hydrogen supply.